1999
DOI: 10.1049/el:19990173
|View full text |Cite
|
Sign up to set email alerts
|

Linewidth broadening of Er-doped superfluorescentfibre sourceusing long-period grating

Abstract: GEORGES, T., MONERIE, M., and POUMELLEC, B.: 'Behaviour of spectral transmissions of Bragg gratings written in germania-doped fibres : Writing and erasing experiments using pulsed or CW uv exposure',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…High output power SFS are reported using Er-doped single mode and multimode fibres [16,23]. Long period grating (LPG) has been used with SFS for multiwavelength generation [24], broadening the fluorescence band [25] and to compensate the dependence of mean wavelength of ASE on temperature [26].…”
Section: Introductionmentioning
confidence: 99%
“…High output power SFS are reported using Er-doped single mode and multimode fibres [16,23]. Long period grating (LPG) has been used with SFS for multiwavelength generation [24], broadening the fluorescence band [25] and to compensate the dependence of mean wavelength of ASE on temperature [26].…”
Section: Introductionmentioning
confidence: 99%
“…It is indicated that by inserting an appropriate LPG the linewidth of a DPB SFS with single-humped band at 1558 nm could be increased almost as much as two times over a large pump power region with only little power loss [27]. Here we further discuss the mean wavelength stability of such a DPB SFS using the same LPG's.…”
Section: Experiments Resultsmentioning
confidence: 89%
“…LPGs were extensively studied for many practical applications such as band rejection filters [1] or, in cascaded configuration, as coaxial fiber interferometers [2]; LPGs have been also used for wavelength division multiplexing [3], many types of fiber sensors [4], gain equalizers in erbium doped fiber amplifiers [5], etc. Nowadays, because of surge of a practical interest in rare-earth doped fiber lasers and amplifiers, LPGs have been found some new applications as, for instance, tunable optical filters [6,7], pump power management in cladding pumped fiber lasers [8] and control of the operation wavelength [9].…”
Section: Introductionmentioning
confidence: 99%